1987
DOI: 10.1152/jappl.1987.62.3.946
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of dorsal and ventral respiratory group neurons by phrenic nerve afferents

Abstract: The projections of phrenic nerve afferents to neurons in the dorsal (DRG) and ventral (VRG) respiratory group were studied in anesthetized, paralyzed, and vagotomized cats. Extracellular recordings of neuronal responses to vagal nerve and cervical phrenic nerve stimulation (CPNS) indicated that about one-fourth of the DRG respiratory-modulated neurons were excited by phrenic nerve afferents with an onset latency of approximately 20 ms. In addition, non-respiratory-modulated neurons within the DRG were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…However, in a few supplemental experiments, we could not detect any rapid (i.e., within 1-3 breaths) changes in the EMG activity of the contralateral hemidiaphragm or external intercostal muscles following phrenicotomy. Phrenic afferents are also capable of exerting excitatory effects on supraspinal respiratory neurons (44). Consistent with this notion, we noted that phrenicotomy induced immediate changes in respiratory frequency in uninjured rats.…”
Section: Discussionsupporting
confidence: 86%
“…However, in a few supplemental experiments, we could not detect any rapid (i.e., within 1-3 breaths) changes in the EMG activity of the contralateral hemidiaphragm or external intercostal muscles following phrenicotomy. Phrenic afferents are also capable of exerting excitatory effects on supraspinal respiratory neurons (44). Consistent with this notion, we noted that phrenicotomy induced immediate changes in respiratory frequency in uninjured rats.…”
Section: Discussionsupporting
confidence: 86%
“…Since 5-HT does not cross the blood-brain barrier [26], increase in central inspiratory drive cannot be ascribed to any direct action of this agent on medullary respiratory neurons. Diaphragmatic afferents were still present in all animals of the present study, and some observations in cats [25] and dogs [10] have shown that their activation by the increase in strength of diaphragmatic contraction, as produced by resistive loading, exerts facilitatory influences on the respiratory centers.…”
Section: Changes In Central Inspiratory Drivesupporting
confidence: 53%
“…On the other hand, activation of phrenic afferents may stimulate breathing in some cases. Speck and Revellete (64) showed that about one-fourth of dorsal respiratory group respiratory-modulated neurons are excited by phrenic afferents. Based on conduction velocity measurements, they attributed this effect to activation of predominantly small, type III myelinated fibers.…”
Section: Axotomy Of Phrenic Motoneurons and Afferent Neurons: Potentimentioning
confidence: 99%